Colchicine as A Potential Therapy in Hepatocellular Carcinoma: A Review - Gembong Satria Mahardhika; Azizah Nurul Ilmi; I Gede Arinton; Suharno Suharno (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Liver cancer is the seventh most common cancer and the fourth leading cause of cancer death worldwide. Hepatocellular carcinoma (HCC) is a challenging disease to treat and has a poor prognosis. Colchicine is an old drug that was recently found to have anticancer activities towards several cancer cells. This article aimed to review the potential properties of colchicine as chemotherapy for HCC.Methods: The literature review was done by searching databases from PubMed, Cochrane, and ProQuest from June 4th to 26th, 2021. Full-text articles were searched by literature search strategies. The articles were screened by abstract and title. Studies that met the criteria were screened for full text.Results: Forty-six articles were identified, seven articles were screened for titles and abstracts, and three articles were excluded owing to full-text unavailability. Four articles were reviewed.Conclusions: The potential of colchicine as a preventive therapy in HCC needs to be further explored, and additional tests need to be done, especially in vivo. Larger population studies should also be done to evaluate the safety, usefulness, and feasibility of colchicine, especially in HCC.